Efficacy of selective serotonin reuptake inhibitors in the absence of side effects: a mega-analysis of citalopram and paroxetine in adult depression. Issue 8 (August 2018) - Hieronymus, F; Lisinski, A; Nilsson, S; Eriksson, E
Abstract It has been suggested that the superiority of antidepressants over placebo in controlled trials is merely a consequence of side effects enhancing the expectation of improvement by making the patient realize that he/she is not on placebo. We explored this hypothesis in a patient-level post hoc-analysis including all industry-sponsored, Food and Drug Administration-registered placebo-controlled trials of citalopram or paroxetine in adult major depression that used the Hamilton Depression Rating Scale (HDRS) and included a week 6 symptom assessment (n =15). The primary analyses, which compared completers on active treatment without early adverse events to completers on placebo (with or without adverse events) with respect to reduction in the HDRS depressed mood item showed larger symptom reduction in patients given active treatment, the effect sizes being 0.48 for citalopram and 0.33 for paroxetine. In actively treated subjects reporting early adverse events, who also outperformed those given placebo, the severity of the adverse events did not predict response. Several sensitivity analyses, for example, including (i) those using change of the sum of all HDRS-17 items as effect parameter, (ii) those excluding all subjects with adverse events (that is, also those on placebo) and (iii) those based on the intention-to-treat population, were all in line with the primary analyses. The finding that both paroxetine and citalopram are clearly superior to placebo also when not producing adverse events, as well as the lack of association between adverse event severity and response, argue against the theory that antidepressants outperform placebo solely or largely because of their side effects.